Microstructure and mechanical properties of porous aluminium composites reinforced with diamond particles - Parveez, Bisma; Jamal, Nur Ayuni; Mohamad Kadri, Syazwan; Ahmad Azhar, Ahmad Zahirani; Mohd Zaki, Hafizah Hanim (Springer, 2023)
n the present work, diamond particles with various contents (5, 10 and 15 wt. %) were reinforced in porous aluminum (Al) composite via powder metallurgy technique. The desirable porous structure was designed by incorporating polymethylmethacrylate (PMMA) as a space holder material at fixed content of 30 wt. % in all the composites. Morphology of the resultant porous Al composite demonstrated the formation of uniform closed-cell macropores and diamond particles that are well bonded within the Al matrix. However, higher weight percentage (wt.%) of diamond content resulted in appearances of agglomeration and improper pore. X-ray diffraction (XRD) analysis confirmed strengthening intermetallic phases at the interfaces, thus improving the bonding strength and wetting action. The composites with 5wt.% and 10wt.% diamond content exhibited better compressive properties.